The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11906-021-01141-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypertensive Pregnancy Disorders and Mental and Behavioral Disorders in the Offspring: a Review

Abstract: Purpose of Review We review here recent original research and meta-analytic evidence on the associations of maternal hypertensive pregnancy disorders and mental and behavioral disorders in the offspring. Recent Findings Seven meta-analyses and 11 of 16 original research studies published since 2015 showed significant associations between maternal hypertensive pregnancy disorders and offspring mental and behavioral disorders. Evidence was most consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…[9][10][11][12][13][14] Finally, both GD and GHT have been associated with attention-deficit/hyperactivity disorder and autism in offspring. 3,4,15 Although rates of GD and PE have not been shown to differ by fetal sex, previous literature supports a sex-specific differential response to these conditions. For example, one study 16 found that male but not female offspring born to women with GD were at greater risk of child overweight or obesity at ages 5 to 7 years.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[9][10][11][12][13][14] Finally, both GD and GHT have been associated with attention-deficit/hyperactivity disorder and autism in offspring. 3,4,15 Although rates of GD and PE have not been shown to differ by fetal sex, previous literature supports a sex-specific differential response to these conditions. For example, one study 16 found that male but not female offspring born to women with GD were at greater risk of child overweight or obesity at ages 5 to 7 years.…”
Section: Introductionmentioning
confidence: 92%
“… 9 , 10 , 11 , 12 , 13 , 14 Finally, both GD and GHT have been associated with attention-deficit/hyperactivity disorder and autism in offspring. 3 , 4 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrating that offspring exposure to HDP in utero is associated with metabolic syndrome, 6 mental and behavioral disorders, 7 asthma, 8 and other conditions. Several reviews have shown that offspring born to mothers with HDP have higher blood pressure (BP).…”
Section: Introductionmentioning
confidence: 97%
“…HDP are divided into hypertension known before pregnancy or present in the first 20 weeks, including chronic hypertension, white‐coat hypertension, and masked hypertension, and hypertension arising de novo at or after 20 weeks, including gestational hypertension (GH), preeclampsia (PE) de novo or superimposed on chronic hypertension, and transient GH 5 . Previous studies have confirmed that women who develop HDP have an increased risk of cardiovascular disease later in life, while there have been studies demonstrating that offspring exposure to HDP in utero is associated with metabolic syndrome, 6 mental and behavioral disorders, 7 asthma, 8 and other conditions. Several reviews have shown that offspring born to mothers with HDP have higher blood pressure (BP) 9 .…”
Section: Introductionmentioning
confidence: 99%